Analysis of Medical Equipment Management in Relation to the Mandatory Medical Equipment Safety Manager (MESM) in Japan. Issue 3 (5th September 2014) - Ishida, Kai; Hirose, Minoru; Fujiwara, Kousaku; Tsuruta, Harukazu; Ikeda, Noriaki
Abstract : Half a decade has passed since the fifth revision of the medical law and mandatory appointment of a medical equipment safety manager (MESM) in hospitals in Japan. During this period, circumstances have changed regarding maintenance of medical equipment (ME). We conducted a survey to examine these changes and the current situation in ME management. Maintenance of ME and related work were found to have increased in many hospitals, but the number of clinical engineering technologists (CETs) has only slightly increased. The appointed MESM was a CET or physician in most hospitals. In hospitals where physicians were appointed as the MESM, 81% had operation managers. Many respondents commented that it was difficult for one person to cover all the tasks required by the MESM, due to a lack of knowledge, too much work, or other reasons. This suggests the importance of an operation manager for ME to work under the MESM.